Positioning a mobile robot in a closed area with a map of markers - Sokolov, Oleksandr; Mreła, Aleksandra; Józefowicz, Mateusz; Rydel, Krzysztof; Meszyński, Sebastian (Journal of Education, Health and Sport, 2019)
The article presents issues related to the positioning of mobile robots in a closed area. The method of positioning using photogrammetry methods based on the analysis of specially created unique square-shaped markers is presented. On the basis on such markers placed in the global coordinate system in a closed space (on the terrain ceiling), the proposed algorithms for calculating the spatial and angular positions of the robot are shown. The positioning methods along with the analysis of measurement errors are analyzed. The result of the research is to develop a real-time robot navigation method in the ReMY simulation game.